FAMILY SUPPORT, MOTIVATION, AND THE ATTENDANCE LEVEL OF THE PATIENTS WITH THE CHRONIC NON-COMMUNICABLE DISEASE IN THE CHRONIC DISEASE MANAGEMENT PROGRAM (PROLANIS) - Diana, Meli; Putra, Kusuma Wijaya Ridi; Wijayanti, Dini Prastyo; Riesmiyatiningdyah, Riesmiyatiningdyah; Yumiati, Yumiati (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The quality of life of people with chronic non-communicable diseases can be improved by establishing the Chronic Disease Management Program (PROLANIS). Many factors may affect the presence of chronic non-communicable disease sufferers in PROLANIS activities, including social support, motivation, level of knowledge, work, and others. Objective: This study aimed to analyze the relationship between family support, motivation, and the attendance level of patients with chronic non-communicable diseases in the PROLANIS. Methods: The research design used in this study is an analytical descriptive with a cross-sectional approach. The research was conducted from August 2020 to February 2021 at the FKTP Clinic DKT 02 Sidoarjo. The target population in this study were all 55 members of PROLANIS registered at the FKTP Clinic DKT 02 Sidoarjo. The sampling technique used is total sampling, so that the sample in this study is all members of PROLANIS who are in the target population. In this study, there are 3 variables: family support, motivation, and the attendance of patients who suffer from chronic non-communicable diseases in participating in PROLANIS. The instrument used to measure the attendance of the patients who suffer from chronic non-communicable diseases in participating in PROLANIS is the attendance list in the implementation of PROLANIS for 5 meetings. Meanwhile, the instrument used to measure family support, and motivation of patients suffering from chronic non-communicable diseases following PROLANIS was a close-ended questionnaire. This study used Spearmen Rho statistical test with a significant level of .05 (α < .05). Results: The results showed a relationship between family support and the motivation of patients with chronic non-communicable diseases to participate in the PROLANIS (r = .986; p-value = .000). The results also showed that there was no relationship between family support (r = .187; p-value = .173) and motivation (r = .195); p-value = 153) with the attendance level of the patients with chronic non-communicable diseases in the PROLANIS. Conclusion: The health workers must know what factors can affect their attendance level in PROLANIS activities. By knowing these factors, health workers can make action plans to increase the attendance of chronic non-communicable disease patients in PROLANIS activities.